Peningkatan Kualitas Lada Putih dengan Kombinasi Lama Perendaman dan Penambahan Daun Karamunting (Melastoma malabathricum): Peningkatan Kualitas Lada Putih dengan Kombinasi Lama Perendaman dan Penambahan Daun Karamunting (Melastoma malabathricum) - Yasa Putri; Riwan Kusmiadi; Sitti Nurul Aini (AGROSAINSTEK: Jurnal Ilmu dan Teknologi Pertanian, 2018)
Pepper submersion period with addition karamunting leaf (Melastoma malabathricum) is one expected postharvest to increasing white pepper quality. This research aims to know the influence of submersion period and karamunting leaf dose and also it is interaction to white pepper quality. This research was conducted at Balunijuk village, Bangka Regency and quality testing in UPTD Hall, Certification And Quality Control, Departement of Industry and Commerce Bangka Belitung Island. This research used Randomized Completely Design with 2 factors and F-test. The first factor (P) submersion period: (P0) as control 14 days, (P1) 9 days, (P2) 7 days and (P3) 5 days and two factor add karamunting leaf doses (K): (K0) as control without add karamunting leaf dose 0 g, (K1) 1 00 g, (K2) 150 g, and (K3) 200 g. Each unit of and using 2 kg of fruit pepper. Further testing used Duncan Multiple Range Test with 95% level of confidence. The result showed submersion periods have the significant effect for foreign object, white pepper level, and atsiri oil content. 5 days submersion had the best yield on atsiri oil content (2.44%). There is no interaction between submersion periods by adding karamunting leaf to the quality of white pepper.